Um sistema de monitoramento de computador e vídeo game para profilaxia de Dort/Ler - Saravia, Edgard Gregory Torres (2008)
Two systems to control the computer s and video game s use were developed on this work. By using a database for the control of the computer in which the restrictions of use for each user will be stored, and having as a graphic interface and agenda which will allow the administrator to interact with the system. Yet on this control of computer s use, the entire system will be controlled through a device that will be linked to the computer. The repealing of this device will be explained as a violation to the program, what will be stored in the database too, the administrator will have the mastery on all the information that an average user does. At any moment, the administrator will be able to print a report about what each user did. As far as the control of the domestic plug of energy, the administrator will be able to insert a determined restriction for each kind of plug. The control will also be done by using a microcontroller, and the data will be sent from the USB protocol. The devices were tested and were taken as efficient systems, although as future work will be able to be implemented a system, which, through the help of a computer, will be able to become available a schedule for a specific user, according to presented damages.